Study of the composition of the goutweed flowers essential oil, its renal effects and influence on uric acid exchange - Koyro, O.O.; Tovchiga, O.V.; Stepanova, S. I.; Shtrygol, S. Yu. (Pharmacognosy Communications)
The composition of the goutweed flower essential oil from Kharkiv region (Ukraine) was studied using gas chromatography-mass spectrometry. Sesquiterpenes have been found to be the main group of the essential oil. The principal compounds contained in the oil were β-farnesene (43.94%), α-bergamoten (15.32%), (E, E)-α-farnesene (8.84%) and 1,5,9,9-tetramethyl-1,4,7-cycloundecatrien (5.51%). Diuretic and uricosuric activity of the goutweed flower essential oil in a dose of 1 ml/kg has been determined for the first time. It has been shown that the single dose increases creatinine, urea and uric excretion with the urine volume being unchanged. In the course of administration, a diuretic effect appears, creatinine excretion returns to the initial state while urea and uric acid excretion decreases. No significant differences between the effects of the aforesaid essential oil and the reference drug olimetin are observed. Thus, the essential oil may be involved in the diuretic and uricosuric activity of goutweed.
Keywords: Aegopodium podagraria L.; goutweed; diuretic agents; essential oil; uricosuric agents; uric acid